Attitudes of intensive care and emergency physicians in Australia with regard to the organ donation process: A qualitative analysis. (September 2020) - Macvean, Emily; Yuen, Eva YN; Tooley, Gregory; Gardiner, Heather M; Knight, Tess
Specialized hospital physicians have direct capacity to impact Australia's sub-optimal organ donation rates because of their responsibility to identify and facilitate donation opportunities. Australian physicians' attitudes toward this responsibility are examined. A total of 12 intensive care unit and three emergency department physicians were interviewed using a constructionist grounded theory and situational analysis approach. A major theme emerged, related to physicians' conflicts of interest in maintaining patients'/next-of-kin's best interests and a sense of duty-of-care in this context. Two sub-themes related to this main theme were identified as follows: (1) discussions about organ donation and who is best to carry these out and (2) determining whether organ donation is part of end-of-life care; including the avoidance of non-therapeutic ventilation; and some reluctance to follow clinical triggers in the emergency department. Overall, participants indicated strong support for organ donation but would not consider it part of end-of-life care, representing a major obstacle to the support of potential donation opportunities. Findings have implications for physician education and training. Continued efforts are needed to integrate the potential for organ donation into end-of-life care within intensive care units and emergency departments.